2014 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM 2014) 2014
DOI: 10.1109/asonam.2014.6921607
|View full text |Cite
|
Sign up to set email alerts
|

Joint voting prediction for questions and answers in CQA

Abstract: Abstract-Community Question Answering (CQA) sites have become valuable repositories that host a massive volume of human knowledge. How can we detect a high-value answer which clears the doubts of many users? Can we tell the user if the question s/he is posting would attract a good answer? In this paper, we aim to answer these questions from the perspective of the voting outcome by the site users. Our key observation is that the voting score of an answer is strongly positively correlated with that of its questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These works used textual and nontextual features to evaluate quality. Some research also evaluated answer quality based on question quality, finding a high correlation between the two (Yao et al, ; Arora, Ganguly, & Jones, ). Different advance machine learning techniques such as random forest and deep neural network are applied to find the quality of contents in CQA and the users who fail to generate the good content (Chen et al, ; Le, Shah, & Choi, ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…These works used textual and nontextual features to evaluate quality. Some research also evaluated answer quality based on question quality, finding a high correlation between the two (Yao et al, ; Arora, Ganguly, & Jones, ). Different advance machine learning techniques such as random forest and deep neural network are applied to find the quality of contents in CQA and the users who fail to generate the good content (Chen et al, ; Le, Shah, & Choi, ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Very few studies have quantitatively examined the part-whole relationships for the purpose of prediction. In CQA sites, empirical studies have shown a strong correlation between the question voting score and the average/maximum answer voting score [22]. Based on this observation, a joint predictive model that leverages question/answer coupling is proposed that is also able to capture the dynamics of the community posts [23].…”
Section: Related Workmentioning
confidence: 99%
“…First (Modeling Challenge), the relationship between the parts outcome and whole outcome might be complicated, beyond the simple addition or linear combination. For example, the authors in [22] empirically identi ed a non-linear correlation between the impacts of questions and the associated answers, that is, the impact of a question is much more strongly correlated with that of the best answer it receives, compared with the average impact of its associated answers. However, how to leverage such non-linear relationship between the parts and whole outcome has largely remained open.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we focus on the voting score prediction of questions/answers shortly after they are posted in the CQA sites. Such a task is essential for the prosperity and sustainability of the CQA ecosystem, and it may benefit all types of users, including the information producers and consumers [2]. For example, detecting potentially high-score answers can benefit the questioners as well as the people who have similar questions; it would also be helpful to identify high-score questions in the early stage and route them to expert answerers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, detecting potentially high-score answers can benefit the questioners as well as the people who have similar questions; it would also be helpful to identify high-score questions in the early stage and route them to expert answerers. Generally speaking, there are three key aspects that matter with the voting prediction of a post, namely, (1) the non-linearity between features and output, (2) the coupling between questions and answers, and (3) the dynamics (of training data sets). First, both the contextual features (e.g., the reputation of the user who issues the question, etc.)…”
Section: Introductionmentioning
confidence: 99%